2019
DOI: 10.2196/14241
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Internet Use Among Men With Prostate Cancer in Canada: Cancer Registry Survey Study

Abstract: BackgroundAfter a prostate cancer diagnosis, men want information about their disease and treatment options. The internet offers a convenient means to deliver health information to patients with prostate cancer. However, there are concerns about the use of the internet among this largely senior population.ObjectiveThis study aimed to determine the patterns and factors associated with the use of the internet as a source of health information among Canadian men with prostate cancer and the features and informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Health information is obtained from various sources. The Internet is an attractive and common source of health information today [16,28,31]. The use of the internet to access health information has increased in recent years due to the reasons such as accessibility, high volume of information disseminated trough that, confidentiality, low cost, multi-media capabilities and the ability to interact and to gain support [24,27,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health information is obtained from various sources. The Internet is an attractive and common source of health information today [16,28,31]. The use of the internet to access health information has increased in recent years due to the reasons such as accessibility, high volume of information disseminated trough that, confidentiality, low cost, multi-media capabilities and the ability to interact and to gain support [24,27,32].…”
Section: Resultsmentioning
confidence: 99%
“…It has dramatically changed information behavior from passive information receiving from statistic sources such as books to active information seeking from dynamic and user-contributed sources such as online blogs and forums [14]. Internet provides an easy and cost-effective source of health information for peoples [15,16]. Using internet for healthrelated applications is so widespread that it said searching health information has become the most common use of this technology [1, 3,17].…”
mentioning
confidence: 99%
“…Many patients decide to combine multiple sources to fulfill their needs. Generally, 25% to 83% of patients search for online health information before or after a consultation with their medical expert [ 33 - 36 ]. Patients seem to use online health information in addition to a consultation to prepare themselves [ 13 ], to complement the information given by the medical expert [ 13 , 24 , 25 ], as well as to validate or challenge the information given by the medical expert [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,16 In contrast, in a population-based study of prostate cancer survivors in Canada, age, education, and income did not play a significant role in determining health-related Internet use when other factors were considered. 18 Instead, being an active information seeker, having higher eHealth confidence, and broadband access were the strongest determinants of health-related Internet use. 18 Notably, Dee et al 4 found that cancer survivors who were very dissatisfied with their healthcare were 78% more likely to use the Internet as a health information source when compared with those who were satisfied and that this association was greater among women.…”
mentioning
confidence: 98%
“…18 Instead, being an active information seeker, having higher eHealth confidence, and broadband access were the strongest determinants of health-related Internet use. 18 Notably, Dee et al 4 found that cancer survivors who were very dissatisfied with their healthcare were 78% more likely to use the Internet as a health information source when compared with those who were satisfied and that this association was greater among women. Previous research has shown that women tend to be less satisfied with their healthcare 19,20 and more likely to seek health information on the internet than men.…”
mentioning
confidence: 98%